A Technical Note on Fabrication and Thermal Performance Studies of a Solar Pond Model. (14th March 2013) - Saxena, Abhishek; Goel, Varun
Abstract : A solar pond has been fabricated to analyze the thermal behavior of it, in the climatic conditions of Moradabad, Uttar Pradesh. Sodium chloride (NaCl) has been used to form a salt gradient for better performance, and a dark-colored (blackened) rigid surface bottom with 1 mm irregularities has been considered for trapping the heat in a good amount. A solar pond with a surface area of 2.56 m 2 and a depth of 1 m has been filled with salty water of various densities to form three salty water zones (upper convective, nonconvective, and heat storage). A few investigations have been carried out to evaluate the thermal efficiencies of three different zones of the solar pond. An attempt is also made to improve the thermal performance of the salt gradient solar pond.